The Purple Puffy Coat - Boelts, Maribeth 1964-; Duncan, Daniel (Somerville, Massachusetts : Candlewick Press, 2020)
"Beetle gives Stick Bug an attention-grabbing coat for his birthday--but is that what Stick Bug really wants? A delightful story about friends learning to understand each other."--
Keywords: Friendship -- Juvenile fiction; Birthdays -- Juvenile fiction; Gifts; Juvenile fiction; Individual differences; Juvenile fiction; Fiction